CGIAR Initiative on Diversification in East and Southern Africa and CGIAR Initiative on Gender Equality: Stakeholder Consultation Workshop - Anbacha, A.; Mapedza, Everisto D.; Joshi, Deepa; Nigussie, Likimyelesh; Puskur, R.; Nchanji, E.; Mukhopadhyay, P.; Nortje, Karen; Enokenwa Baa, Ojongetakah; Jacobs-Mata, Inga; Zewde, Y.; Ketema, Dessalegn Molla; et al. (CGIAR Initiative on Diversification in East and Southern Africa, 2023)
A stakeholder consultation workshop was conducted by the CGIAR Initiatives on Diversification in East and Southern Africa (Ukama Ustawi) and Gender Equality on 31 January 2023 at the International Livestock Research Institute (ILRI), Addis Ababa, Ethiopia. The workshop aimed to identify and address barriers that limit participation of women and youth and how these are addressed in an ongoing "Veggies for People and Planet" program at the World Vegetable Center. The workshop also sought to investigate existing opportunities and recommend possible integrated solutions for more equitable and inclusive value chain development.